Changes on fruit quality characteristics during developing period of tomato - Carvalho, Vânia Déa de; Chalfoun, Sára Maria; Paula, Miralda Bueno de; Rosa, Luciano de Assis (Pesquisa Agropecuaria Brasileira, 2014)
The contents of some physical-chemical and chemical constituents in tomato fruits (Lycopersicon esculentum Mill.) of Gigante Kada cultivar harvested at eight stages of the fruit developing period were determined. This work aimed to determine the changes occurred in these constituents during this period. It was observed that: a) the total solids, titratable acidity and C vitamin contents did not change during fruit developing period; b) soluble solids, reducing sugars and soluble solids acidity ratio values increased until they reached the highest levels at the 4th stage (3.36 cm of medium diameter); after then, these values decreased; c) pH values decreased after the 4th stage of fruit developing; d) the highest contents of monomeric, di- and oligomeric and total phenolic compounds were presented by fruits on the 1st stages of developing period (with about 1.8 cm of diameter); e) the full development of fruits can be evaluated by pH (4,7%) and reducing sugars (2,2%) values.